Multicultural Modernism: Architectural Balance in a Changing World - Steven Ehrlich (Oz, 2009)
The beginning of the 21st century finds man facing critical issues which affect our continued coexistence on this planet. These include: meshing the colliding cultures of the global village created by jet travel and modern telecommunications; reconciling surging economic growth with the need to repair and sustain our already-damaged natural environment; aiding the “have-not” peoples and countries in an increasingly stratified world; and providing refuge from the stresses and clamor of the marketplace, the media and our increasingly urban lives.